Report of the Task Force Identification of Districts for Wage & Self Employment Programmes - Planning Commission (Planning Commission, 2003)
The Task Force on Identification of Districts for Wage and Self Employment Programmes, established by the Ministry of Rural Development in 2001, aimed to enhance employment opportunities in India’s backward districts, particularly during lean agricultural seasons. Using parameters such as poverty incidence, agricultural wages, productivity, SC/ST population, and environmental factors, 447 districts were analyzed, and 150 districts—mainly in central and eastern India—were identified for intensive wage-employment programmes. Self-employment initiatives were recommended for implementation across all districts to leverage the potential of self-help groups. The analysis of agricultural wages and the District Index of Backwardness revealed significant disparities, highlighting regions with low wages and productivity, underscoring the need for targeted, data-driven interventions. The report emphasizes continuous monitoring, equitable resource allocation, and policy measures to improve rural livelihoods, enhance agricultural productivity, and promote balanced regional development.
Planning Commission May 2003
Planning Commission
Keywords: Wage Employment; Self Employment; Backward Districts; Rural Development; Poverty Alleviation; Agricultural Wages; SC/ST Population; District Index of Backwardness; Employment Programmes; Policy Recommendations; Targeted Interventions; India